A Study on Tapentadol Misuse and Abuse among Heroin Users Attending a Deaddiction Center in Kashmir - Marya Zahoor; Fazle Roub Bhat; Ubaid Ali Khan; Yasir Hassan Rather (Indian Journal of Social Psychiatry, 2025)
Background: Tapentadol is a powerful opioid receptor agonist and a norepinephrine reuptake inhibitor, making it a centrally acting analgesic. In India, where the government is trying to combat an ongoing opioid crisis, the lack of scheduling of tapentadol creates an easy opportunity for its misuse. We aim to analyze the demographic and clinical characteristics of heroin users who also abuse tapentadol concurrently through our cross-sectional study done at the drug-deaddiction center situated at the community center of SMHS Hospital, Srinagar, Kashmir. Material and Methods: It was a cross-sectional study done at the Community Centre of SMHS hospital Srinagar, which houses the drug deaddiction centre run by the Psychiatry Department of GMC(Government Medical College) Srinagar. From 1st June 2023 until 30th November 2023, we gathered data for our investigation. After gaining informed consent, all the first-time heroin-dependent patients at the deaddiction facility who admitted to using tapentadol were included in the study. Patients' age, sex, marital status, family composition, and level of education were analysed in accordance with a predefined proforma. In addition, the modified Kuppuswamy scale was used to categorise patients based on their socioeconomic status. Parameters such as the pattern of tapentadol use, the route of heroin use, and the comparison of the psychoactive effects of tapentadol and heroin were recorded using a proforma to create a clinical profile of such patients. Results: Our sample comprised 100 participants. The prevalence of tapentadol abuse among heroin users in our study came out to be 16%. The average age of our study participants was 25.11 ± 2.99 years. The vast majority of our patients were male (97%). The vast majority (58%) of our participants were from lower socioeconomic status. Ninety-eight percent of our subjects used oral tapentadol while there were 2 (2%) instances of intravenous tapentadol use. The majority of participants used the “Tapal” brand (60%). Tapentadol was mainly obtained either through a chemist’s shop (35%) (with or without a prescription) or through a friend (37%). Half of the subjects (50%) obtained tapentadol for the purpose of managing heroin withdrawal. Thirty-five percent of participants used tapentadol in a dependent manner, while the remaining 65% either misused or abused the drug. Conclusion: The continued heroin usage crisis, lenient tapentadol procurement regulations, and the use of nonevidence-based drugs for the treatment of opioid use disorder all contribute to the problem of tapentadol abuse in our region.